The Summary of an Urdu Version of Diabetes Self-Care Activities Measure: Psychometric Evaluation and Validation - Rashid M. Ansari; Mark F. Harris; Hassan Hosseinzadeh; Nicholas Zwar (SAGE Publishing, 2020)
Objective: The English version of the Summary of Diabetes Self-Care Activities (SDSCA) measure is the most frequently used self-reporting instrument assessing diabetes self-management. This study is aimed at translating English SDSCA into the Urdu version and validating and evaluating its psychometric properties. Methods: The Urdu version of SDSCA was developed based on the guidelines provided by the World Health Organization for translation and adaptation of instruments. The panel of experts examined the content validity, reliability, and internal consistency of the instrument. The translation process from the English version to the Urdu version revealed excellent results at all the stages. Results: The instrument showed promising and acceptable results. Of particular mention are the results related to split-half reliability coefficient 0.90, test-retest reliability ( r = 0.918, P < .001), intraclass coefficient (0.912), and Cronbach's alpha (.79). The factor analysis (exploratory and confirmatory) was not performed in this study due to the small sample size (n = 30) as the objective was to validate the Urdu version of the SDSCA instrument. Conclusions: This study provided evidence for the reliability and validity of the Urdu Summary of Diabetes Self-Care Activities (U-SDSCA) instrument, which may be used in the future for the patients of diabetes in order to assess type 2 diabetes self-management activities in the rural area of Pakistan and other Urdu-speaking countries.